Antecedents of green purchasing behavior among Malaysian consumers - Sinnappan, Punitha; Abd Rahman, Azmawani (Medwell Online, 2011)
The purpose of this study is to examine the factors that influence green purchasing behaviors of Malaysian consumers and observes if the factors affecting green purchasing behavior differ by demographic profile. Respondents in this study were consumers from various age groups, education level, ethnic group, type of occupation and income level. The results shows that the best predictor for green purchasing behavior is environmental attitude followed by perceived environmental responsibility; environmental concern, perceived seriousness of environmental problems, perceived effectiveness of environmental behavior and government’s role. While for demographic variables, only age group is significant in explaining the environmental factors. The result of the research can serve as a guideline for firms to strategize their marketing approaches that caused buying behavior while analyzing the demographic characteristics would give firms better knowledge towards targeting these groups of people. This study also offers practical guidelines to marketers who are planning to target the Malaysian market. The understanding on the changing consumption pattern of Malaysian consumers and the value of attachment, they gave to the environment provides useful insights that are especially pertinent to an improved understanding of green purchasing behavior in the South East Asia context.